Role of Lung Ultrasound in Diagnosis of Ventilator Associated Pneumonia - Rabea, Mohamed Abd-Elkareem; Elharrisi, Mona Abdel Hamid; Gamil, Neven Mohamed; Mohamed, Mohamed lofty; Nada, Mohamed Gamal (Journal of Neonatal Surgery, 2025)
Lung ultrasound (LUS) has emerged as a valuable bedside imaging modality in critically ill patients, offering a rapid, non-invasive, and radiation-free alternative to chest X-ray and CT scan. It enables early detection of pulmonary pathologies such as pneumothorax, pleural effusion, pulmonary edema, consolidation, and interstitial syndrome. The increasing accuracy and availability of ultrasound devices have expanded its role in anesthesia, intensive care, and emergency medicine